Control Strategy Used in DFIG and PMSG Based Wind Turbines an Overview - V. Meenakshi; S. Paramasivam (Institute of Advanced Engineering and Science, 2017)
Nowadays, the fossil combustibles are replaced by renewable energies sources .These renewable energies are nontoxic, dirt free, and protected and reasonably cheep for the user. Renewable energy resources like bio-gas, geothermal, solar, tidal waves and wind have been found as the best alternatives energy source. Among those renewable energy sources, wind energy stands foremost for generating electricity. In order to have a constant utilization of wind energy and to extract maximum power from wind energy. In this paper, various control strategies prevalent to both the Doubly Fed Induction Generator (DFIG)and Permanent Magnet Synchronous Generator(PMSG) have been analyzed . In addition, control topology applicable to power electronics converter/inverter used in wind electric generators are discussed.